TELAAH LITERATUR TENTANG ANALISIS RISIKODAN STRATEGI PENGUJIAN PENGENDALIANINTERNAL DALAM PROSES AUDIT - Hera Rahmatin Barokah; Elyanti Rosmanidar; Ayu Mustika Lestari; Dwi Intan Lestari; Fadila Marsyafitri; Medya Nita Sari; Jenny Dwi Rahmawati (ICONS: Islamic Economics Journal, 2025)
This article discusses the importance of risk analysis and the design of internal control testing in the audit process. As organizations face increasingly complex financial environments, auditors are expectedto carry out their work with ahigher level of diligence.The audit process now prioritizes understandingbusiness risks and internal control systems as part of a risk-based audit approach. Through this method,auditors can identify critical areas with potential misstatements and design relevant testing procedures.This study aimsto explain the theoretical framework of risk assessment and internal control testing, and how these elements support the credibility and effectiveness of the audit. Using qualitative research methods with a literature study approach, this article highlights the interrelation between risk analysis and audit strategy formulation, as well as the auditor's role in ensuring accurate and transparent financial reporting.